Potential availability of non-woody biomass feedstock for pellet production within the Republic of Ireland - Nolan, Anthony Laurence (International Journal of Agricultural and Biological Engineering, 2010)
The threat of increasing fuel prices and climate change necessitates the need for clean, renewable and independent energy sources. A GIS (Geographical Information Systems) model was developed using ArcGIS 9.2 to analyze the availability of non-woody biomass (wheat, oat, barley and rape straw, willow and miscanthus) for pellet production in Ireland. Utilization within the heating and electricity sector would displace currently used fossil fuels with cleaner, carbon neutral non-woody residues. The total hectares of biomass within Ireland were computed and the biomass yield determined. The greatest potential source of biomass for pelleting is cereal straw. Within the Republic of Ireland the South-East, South-West and Mid-East of Ireland have the greatest biomass yield for pellet production and likely to be most economically viable. Non-woody biomass has a realistic potential to displace fossil fuels within the heating and electricity sector resulting in CO2 mitigation. Keywords: Biomass pellet production, Non-woody biomass, GIS analysis, Renewable energy source, CO2 mitigation DOI: 10.3965/j.issn.1934-6344.2010.01.0-0 Citation: Anthony Nolan, Kevin Mc Donnell, Ger J. Devlin, John P. Carroll, John Finnan. Potential availability of non-woody biomass feedstock for pellet production within the Republic of Ireland. Int J Agric & Biol Eng, 2010; 3(1): <span style="line-height: 140%; font-family: